Pengelolaan Kewirausahaan Berbasis Digital pada UMKM Furniture - Ni Wayan Rustiarini; Ni Putu Nita Anggraini (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: Digitalization is essential in managing entrepreneurship and can increase time efficiency and work productivity. However, MSME owners have several challenges, such as limited knowledge and skills in implementing digitalization. This community partnership activity aims to increase partner empowerment by conducting three-dimensional product design and digital-based financial records. Method: Service is carried out at Tresna Woodcraft MSMEs involving two partners. The plans include surveys, interviews, discussions, consultations, science and technology substitution, training and mentoring, and monitoring and evaluation. Results: The monitoring and evaluation results showed an increase in the level of skills (92.86%) and knowledge (166.67%) of partners after attending SketchUp and Cash Book training. These results show that community partnership activities have been carried out effectively. Conclusion: This activity improves partners' skills in designing three-dimensional products. Digital financial records also help MSME owners make quick and accurate economic decisions.